Increased prevalence of autoimmune disease within C9 and FTD/MND cohorts: Completing the picture. Issue 6 (December 2016) - Miller, Zachary A.; Sturm, Virginia E.; Camsari, Gamze Balci; Karydas, Anna; Yokoyama, Jennifer S.; Grinberg, Lea T.; Boxer, Adam L.; Rosen, Howard J.; Rankin, Katherine P.; Gorno-Tempini, Maria Luisa; Coppola, Giovanni; Geschwind, Daniel H.; et al.
Abstract : Objective: To determine the prevalence of autoimmune disease in symptomatic C9ORF72 (C9) mutation carriers and frontotemporal dementia with motor neuron disease (FTD/MND) cohorts. Methods: In this case-control study, we reviewed the clinical histories of 66 patients with FTD/MND and 57 symptomatic C9 carriers (24 overlapping cases), a total of 99 charts, for history of autoimmune disease. The prevalence of autoimmune disease in C9 and FTD/MND cohorts was determined by χ 2 and Fisher exact comparisons between the combined C9 and FTD/MND group with normal control, Alzheimer disease, and progressive supranuclear palsy cohorts, as well as comparisons within C9 and FTD/MND cohorts. Results: Our combined C9 and FTD/MND cohort has a 12% prevalence of nonthyroid autoimmune disease. The prevalence of nonthyroid autoimmune disease in C9 and FTD/MND is similar to the rates in previously detailed progranulin and semantic variant primary progressive aphasia cohorts and elevated in comparison to previously collected normal control and typical Alzheimer disease cohorts, as well as a newly screened progressive supranuclear palsy cohort. Furthermore, the types of autoimmune disease in this combined C9 and FTD/MND cohort cluster within the same 3 categories previously described in progranulin and semantic variant primary progressive aphasia: inflammatory arthritides, cutaneous conditions, and gastrointestinal disorders. Conclusions: The association between selective autoimmune disease and neurodegenerative disorders unified by the underlying pathology frontotemporal lobar degeneration with TDP-43–positive inclusions (FTLD-TDP) extends to C9 and FTD/MND cohorts, providing further evidence that select autoimmune inflammation may be intrinsically linked to FTLD-TDP pathophysiology.